Bridging the gap: Boomer librarians lure millennial students to the library - Green, Peter (2007)
Old dogs can learn new tricks and industrious baby boomer librarians can bridge the generation gap with the just-in-time millennial students who form the new wave crashing upon the ancient rock of the library. And millennial students are finding the library is the place to be, as did their parents before them. The library of the Curtin University of Technology has been busy bridging the gap by adapting traditional services to new technology an transforming the physical place of the library into a comfortable blend of the real and the virtual. The library is the place to be courtesy of an aging but energetic profession who are not yet ready to make way.